Investigation of Causal Relationship between Trade Credit and Bank Loan during 2008 Financial Crisis - Ahmed, Jaleel; Xiaofeng, Hui; Virk, Muhammad Usman; Abdullah, Muhammad (Journal of Asian Business Strategy, 2015)
This research paper attempts to investigate the causal relationship between trade credit and bank loan during 2008 financial crisis. After collecting data from 2005 to 2011 we have used Two Stage Least Square (TSLS) estimation technique. We have found that trade credit supply and bank loan are simultaneously determined and have a complementary effect during 2008 financial crisis. On the other side trade credit demand and bank loan are simultaneously determined where bank loan causes trade credit demand to decrease. A substitution effect has been observed between trade credit demand and bank loan during 2008 financial crisis. Net trade credit and bank loan have a positive and significant impact on each other. These relationships are also remains significant as in before and after financial crisis. Financial crisis have a positive impact on trade credit supply and demand. We have also found an inverse relationship between financial crisis and bank loan.